Project NABITASAN Naaayong Alaga Bigay ni Ina Tungo sa Akma at Sapat na Nutrisyon.
Malnutrition is a multifactorial problem continuously plaguing communities around the world. Child malnutrition accounts for more than five million deaths each year worldwide in children below five years. The child?s nutritional status in this age bracket is crucial for their proper growth and development; hence, an urgent need to address the problem. In the Philippines, the incidence and prevalence of malnutrition doubles annually, owing to several factors hindering its rapid eradication. Leganes, Iloilo is listed as one of the top municipalities with the highest number of cases (92 cases) out of its 18 counties. The team aimed to help reduce the high number of cases through Project NABITASAN, an intervention geared to change the mothers? knowledge, attitudes, and practices about proper nutrition and food preparation. A series of lectures and activities were conducted, with the team monitoring their progress and increase in knowledge after every lecture through comparison of pre- and post-tests. A significant increase in the mothers? knowledge was observed in every lecture (Lecture 1: t= -10.472, df=42, p-value<0.001; Lecture 2: t= -7.737, df=36, p-value<0.001; Lecture 3: t= -7.299, df=40, p-value<0.001; Lecture 4: t= -8.615, df=32, p-value<0.001; Lecture 5: t= -10.018, df=38, p-value<0.001). The team prepared fun activities and lectures for the children as well for them to learn about nutrition and its importance. Furthermore, the team facilitated feeding programs in 7 out 8 sitios wherein mothers cooked the children?s breakfast, lunch, and afternoon snacks thrice a week. Vitamins were provided once a week to supplement the feeding sessions. Anthropometric measurements were taken for weekly monitoring. After six weeks, the team was able to reduce malnutrition cases by 65%, with 40 out of 62 children enrolled in the program normalized. Project sustainability was left in the hands of the core group and the barangay council, with the team having drafted a 2017 budget plan proposal to allocate barangay funds for health.